Mapping Various Cooking Oil using Fluorescence Polarization - Ketut Sofjan Firdausi; I. Afiefah; Heri Sugito; Much. Azam (Journal of Physics and Its Applications, 2018)
In this report we have succeeded to map various cooking oils using change of fluorescence polarization. Various cooking oils consisted of several vegetables oils and animal oils (chicken oil and lard) were used in the experiment, and some oils were measured in two different times. The change of polarization angle &tetha; was measured as the difference between linear polarized green pointer laser as incoming light and fluorescence light using a pair of polarizers. The direct measurement of fluorescence polarization gives a new unique result of critical polarizer’s angle φc that can group vegetable cooking oils into group 1 (at φc = 10o for VCO, olive, and soybean), group 2 (at φc = 20o for palm, corn and rice bran), group 3 (at φc = 30o for sunflower and canola), and also animals cooking oils into group 4 (at φc = 20o for chicken oil), and group 5 (at φc = 40o for lard). Mostly cooking oils can be distinguished using modified maps. The large difference φc and &tetha; of lard from vegetable oils provides an advantage to develop for testing halal oil due to lard contamination. The capability of this method has benefits, at least, as a complement and simple method in comparison to other expensive sophisticated instruments such as fluorescence spectroscopy or GCMS methods with their derivation’s instruments.